2021
DOI: 10.1128/aac.02075-20
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Plasmid-Encoded Resistance-Nodulation-Division Efflux Pump in Klebsiella pneumoniae and Klebsiella quasipneumoniae from Patients in China

Abstract: Two multidrug-resistant (MDR) mcr-1 harboring Klebsiella pneumoniae isolates from patients with urinary tract infections, and one MDR Klebsiella quasipneumoniae isolate from a patient with bloodstream infection were identified to carry tmexCD1-toprJ1. The addition of the efflux pump inhibitor reduced the tigecycline MIC against all three isolates by 8- to 16-fold. The pKQBSI104-1 transferred from K. quasipneumoniae to Escherichia coli J53 via conjugation. The tmexCD1-toprJ1-carrying plasmids pKP15ZE495-1 (102,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…Finally, we obtained the complete sequence of pTECL_2-190k-tetX4 from E. cloacae strain TECL_2. The sequence was analyzed using the method mentioned in the previous article ( 12 ). pTECL_2-190k-tetX4 was a 190,185 bp plasmid with three replicon types IncFIA, IncHI1A and IncHI1B, and encoded 220 predicted ORFs ( Fig.…”
Section: Observationmentioning
confidence: 99%
“…Finally, we obtained the complete sequence of pTECL_2-190k-tetX4 from E. cloacae strain TECL_2. The sequence was analyzed using the method mentioned in the previous article ( 12 ). pTECL_2-190k-tetX4 was a 190,185 bp plasmid with three replicon types IncFIA, IncHI1A and IncHI1B, and encoded 220 predicted ORFs ( Fig.…”
Section: Observationmentioning
confidence: 99%
“…Recently, mobile tigecycline resistance genes, tet(X3), tet(X4), and other variants, tet(X5) to tet(X14), encoding flavin-dependent monooxygenases that catalyze tigecycline degradation were emerged in Enterobacterales and Acinetobacter species in China and other countries[4][5][6] . Furthermore, a mobile tigecycline resistance gene cluster, tmexCD-toprJ, encoding the resistancenodulation-cell division (RND) efflux pump that excretes multiple antimicrobials, such as tetracyclines including tigecycline, cephalosporins, fluoroquinolones, and aminoglycosides, emerged predominantly in Enterobacterales: tmexCD1-toprJ1 was identified in plasmids in Klebsiella species isolated from humans and livestock in China and Vietnam[7][8][9] . tmexCD2-toprJ2 was identified in the plasmid and chromosome of Raoultella ornithinolytica isolated from a human in China 10 .A carbapenem-and tigecycline-resistant K. aerogenes isolate NUITM-VK5 was obtained from an urban drainage in Hanoi, Vietnam, in March 2021.…”
mentioning
confidence: 99%
“…This occurrence in different ecological niches indicates that tmexCD1-toprJ1 has disseminated to human, animal and environmental ecosystems and thus has One health ramifications. Other genetic elements driving tmexCD1-toprJ gene, including plasmids (IncX4, IncHI1B, IncQ, IncR, IncHI, plasmid hybrids, and others), insertion sequences (IS 26 , IS 903B , IS Kpn47 , IS Kpn8 , and others), transposon Tn 5393 , and integrons have also been reported ( He et al, 2021 ; Peng et al, 2021 ; Wan et al, 2021 ; Xu et al, 2022 ; Table 3 ). Very recently, variants of the plasmid-encoded transmissible RND efflux pump gene such as tmexCD1-toprJ2 in Rauoltella isolate from a sick Chinese patient ( Wang et al, 2021b ) and tmexCD1-toprJ3 in Klebsiella from urban sludge in Vietnam ( Hirabayashi et al, 2021a ) were reported.…”
Section: Distribution Reservoirs and Traits Of Mobile Tigecycline Res...mentioning
confidence: 99%
“…Nevertheless, the NCBI database revealed that tmexCD1-toprJ gene is already spreading in Europe (United Kingdom), North America (United States), South America (Mexico), Africa (Kenya), and other parts of Asia (Pakistan and India) ( Wang et al, 2021e ). For now, the oldest isolate harboring plasmid-encoded tmexCD1-toprJ is a Klebsiella pneumoniae isolated in 2012 from the urine sample of a 21 year-old woman hospitalized for 21 days because of urinary tract infection ( He et al, 2021 ). Therefore, mobile tmexCD1-toprJ likely emerged since at least a decade ago.…”
Section: Distribution Reservoirs and Traits Of Mobile Tigecycline Res...mentioning
confidence: 99%